Investigation Procedures in Implementing Diversion on Case Against Children's Traffic Accident Police in Purworejo - Mochammad Ipnu Wardani; Akhmad Khisni (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Police as investigators in settling disputes traffic accidents of children, are required to make efforts diversion on. This research problems using a knife analysis theory and the theory of the workings of the criminal responsibility law. Implementation of diversion on by investigators as a form of settling disputes traffic accidents child is in conformity with the provisions of Act No. 11 of 2012 on the Child Criminal Justice System. Investigators obstacles encountered in the application of investigative procedure as a form of settling disputes traffic accidents are children in Purworejo district police diversion on process does not produce an agreement and the diversion on agreement is not implemented. Another constraint is has not formed some infrastructure to support the implementation of the Act SPPA, including the lack of Correctional Centers (BAPAS), Institute of Child Development While (LPAS) and Special Child Development Institute (LPKA) located in the region of Purworejo. In practice, investigators already holding BAPAS Class II Purwokerto, because long distance, it is feared the diversion on process becomes longer than that prescribed by the Act., To overcome these obstacles investigator to approach the families of the victims, seeking coordination with BAPAS and if there is no agreement versioned then handed over to the Prosecutor's case.Keywords: Investigation, Diversion on, Child.